2003
DOI: 10.1128/jvi.77.19.10250-10259.2003
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-Derived Human Immunodeficiency Virus Type 1 p55gagVirus-Like Particles Activate Dendritic Cells (DCs) and Induce Perforin Expression in Gag-Specific CD8+T Cells by Cross-Presentation of DCs

Abstract: To evaluate the immunogenicity of human immunodeficiency virus (HIV) type 1 p55gag virus-like particles (VLPs) released by budding from yeast spheroplasts, we have analyzed the effects of yeast VLPs on monocytederived dendritic cells (DCs). Yeast VLPs were efficiently incorporated into DCs via both macropinocytosis and endocytosis mediated by mannose-recognizing receptors, but not the mannose receptor. The uptake of yeast VLPs induced DC maturation and enhanced cytokine production, notably, interleukin-12 p70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 49 publications
(46 reference statements)
2
50
0
Order By: Relevance
“…These results suggest that PapMV VLPs possess an intrinsic adjuvant-like property that induces DC maturation. Compared to other VLP-based systems, PapMV VLPs seem to be one of the more potent at inducing the upregulation of cosignaling molecules on DCs (15,18,40,41).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that PapMV VLPs possess an intrinsic adjuvant-like property that induces DC maturation. Compared to other VLP-based systems, PapMV VLPs seem to be one of the more potent at inducing the upregulation of cosignaling molecules on DCs (15,18,40,41).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent discordance of these results could be due to a different optimal timing for the sample collection and needs to be evaluated by more extensive observations. Nevertheless, the production of IFN-␥ by DCs induced with enveloped or nonenveloped VLP produced in different expression systems (prokaryotic, yeast, and baculovirus) is still a debated issue (18,28,30,49,53,54). In particular, Yang et al (53), reported that the CD8␣ ϩ…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies will be necessary to evaluate the role of other TLRs in the baculovirus-expressed HIV-VLP-induced activation of MDDCs. Yeast-derived HIV-VLPs have been previously shown to activate MDDCs through the TLR2 (49), suggesting that the expression system used for the VLP production may significantly influence the pathway involved in the biological effects induced on APCs.…”
Section: Cd11cmentioning
confidence: 99%
See 1 more Smart Citation
“…Because yeast exhibits molecular patterns typically associated with pathogens, dendritic cells mature and become activated after receptor-mediated yeast phagocytosis (4). The heterologous tumor antigens expressed in yeast are digested into peptides for presentation via class II and class I MHC receptors that trigger the activation of antigen-specific cytotoxic T lymphocytes (CTL) and helper T cells (4,6,7,11). Prophylactic immunization of mice with ovalbumin-expressing yeast elicited immune-mediated rejection of transplanted ovalbumin-transfected lymphomas or melanomas (Ref.…”
Section: Introductionmentioning
confidence: 99%